Solving Symmetric Inverse Sturm-Liouville Problem Using Chebyshev Polynomials - Neamaty, A.; Akbarpoor, Sh.; Yilmaz, E. (Springer Basel Ag, 2019)
In this study, we consider Sturm-Liouville equation having a symmetric potential function under the separated boundary conditions on a finite interval. Then, we use Chebyshev polynomials of the first kind for calculating the approximate solution of the inverse Sturm-Liouville problem. Finally, we present the numerical results by providing some examples.
Keywords: Inverse problem; Sturm-Liouville operator; symmetric potential; Chebyshev polynomials